ANALISIS PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Susanti, Nelly; Rinadevi, Rinadevi; R, Syahrul; Sukma, Elfia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The curriculum changes that occurred in Indonesia from the 2013 curriculum to the independent curriculum resulted in different approaches used in learning. The 2013 curriculum is known as a scientific approach. Meanwhile, the independent curriculum is also known as the differentiated learning approach. Unfortunately, educators experience difficulties in preparing methods and strategies that are appropriate to this differentiated learning approach. Educators are still confused about accommodating the profiles, learning styles, as well as interests and talents of students in elementary schools. This research aims to describe the analysis of educators' understanding in implementing differentiated learning in Indonesian language subjects in elementary schools and describe the results of the analysis of teachers' activities in implementing differentiated learning in Indonesian language subjects in elementary schools. This research design is a qualitative descriptive research design using observation techniques and filling out questionnaires. Observations were carried out during learning in several schools that were the target of the research. Meanwhile, the questionnaire technique is given by randomly distributing it to educators or elementary school teachers in various regions. The research results show that in general teachers or educators have implemented differentiated learning in Indonesian language subjects in elementary schools. They have been able to create student-centered learning. In addition, the research results also highlight the need for further support and training for educators to develop the skills needed to develop and implement learning strategies that suit the individual needs of students in the classroom as well as measuring achievement in learning Indonesian. The implications of this research emphasize the importance of supporting educators in expanding the repertoire of learning strategies to increase the effectiveness of differentiated learning in basic education environments.